Faktor-Faktor yang Berhubungan dengan Kepatuhan Penderita Kanker Payudara dalam Menjalani Terapi Hormonal di Rumah Sakit Kanker Dharmais Jakarta - Febrianti, Reny Hari; Ratnasari, Febi (Publikasi Indonesia, 2022)
The problem that complicates hormonal therapy in breast cancer patients is that the treatment takes a long time and is regular. Adherence is a factor that determines the effectiveness of a treatment. The impact of the patient's disobedience resulted in the healing process of the disease being hampered. The purpose of this study was to determine the factors associated with the compliance of breast cancer patients in undergoing hormonal therapy. The research method used is descriptive correlation with a cross sectional approach. The results showed that the factors related to the compliance of breast cancer patients in undergoing hormonal therapy were age (p: 0.000), education (p: 0.000), gender (p: 0.000), economic status (p: 0.002), motivation (p: 0.002). p:0.000), knowledge (p:0.000), family support (p:0.000) and the role of nurses (p:0.000). It is hoped that the hospital will improve health promotion, namely providing counseling to breast cancer patients about the importance of undergoing hormonal therapy on a regular basis.